Association between ZFHX3 and PRRX1 Polymorphisms and Atrial Fibrillation Susceptibility from Meta-Analysis. (14th December 2021) - Wu, Liting; Chu, Min; Zhuang, Wenfang
Abstract : Background . Atrial fibrillation (AF) is a common, sustained cardiac arrhythmia. Recent studies have reported an association between ZFHX3/PRRX1 polymorphisms and AF. In this study, a meta-analysis was conducted to confirm these associations. Objective and Methods . The PubMed, Embase, and Wanfang databases were searched, covering all publications before July 20, 2020. Results . Overall, seven articles including 3, 674 cases and 8, 990 healthy controls for ZFHX3 rs2106261 and 1045 cases and 1407 controls for PRRX1 rs3903239 were included. The odds ratio (OR) (95% confidence interval (CI)) was used to assess the associations. Publication bias was calculated using Egger's and Begg's tests. We found that the ZFHX3 rs2106261 polymorphism increased AF risk in Asians (for example, allelic contrast: OR [95% CI]: 1.39 [1.31–1.47], P < 0.001 ). Similarly, strong associations were detected through stratified analysis using source of control and genotype methods (for example, allelic contrast: OR [95% CI]: 1.51 [1.38–1.64], P < 0.001 for HB; OR [95% CI]: 1.31 [1.21–1.41], P < 0.001 for PB; OR [95% CI]: 1.55 [1.33–1.80], P < 0.001 for TaqMan; and OR [95% CI]: 1.31 [1.21–1.41], P < 0.001 for high-resolution melt). In contrast, an inverse relationship was observed between the PRRX1 rs3903239 polymorphism and AF risk (C-allele vs. T-allele: OR [95% CI]: 0.83 [0.77–0.99], P = 0.036 ; CT vs. TT: OR [95% CI]: 0.79 [0.67–0.94], P = 0.006 ). No obvious evidence of publication bias was observed. Conclusions . In summary, our study suggests that the ZFHX3 rs2106261 and PRRX1 rs3903239 polymorphisms are associated with AF risk, and larger case-controls must be carried out to confirm the abovementioned conclusions.